16 Robotic-assisted radical hysterectomy (RRH) for early stage cervical cancer (CC): patterns of recurrence, survival, and the surgeon experience factor. (18th September 2019) - Fitzsimmons, C; Stephens, A; Kennard, J; Manyam, M; Pepe, J; DeCoff, K; Ahmad, S; Mckenzie, N; Kendrick, J; Holloway, R
Abstract : Objectives: To evaluate factors associated with recurrence and survival after RRH for CC. Methods: Pts with early stage CC who underwent RRH(4/2007–12/2017) were evaluated. Inclusion criteria: >one year follow up, adenocarcinoma or squamous carcinoma, stage IA2 or IB1(FIGO 2014 guidelines), and pathologic tumor size(TS) of ≤4 cm. The first 10 learning curve cases per surgeon (A) were compared to all subsequent cases (B). Results: 144 RRH pts were identified and 90 met inclusion criteria. There were 40 A and 50 B patients. Median follow up was 61± 34.3 months (A=71.5, B=52.5). There were 7(7.8%) recurrences with median DFS of 12±8.3 months. Recurrence in A(n=6, 15%) exceeded B(n=1, 2%) (p=0.025). DSDR was 10% A v 2% B(p= 0.184). The 4.5 yr DFS was 84.8%(95 CI±7%) in A v 98%(95 CI ±3%) in B. Positive vaginal margin status(A=10% v B=0%, p=0.034) was the only difference. All recurrences had TS ≥2cm. Of the 42 TS ≥2cm, 5/14(36%) adenocarcinoma recurred compared to 2/28(7%) squamous (p=0.057). Three recurrences had carcinomatosis with mean DFS and OS of 5.3 ±2.3(95% CI ±4.5) and 28.3±30.9(95% CI ±60) months compared to 17.8±6.3(95% CI ±13) and 80.6±48.6(95% CI ±95.2) months for cases with local/pulmonary metastasis(n=4) (p=0.014). Using a multiple logistic regression model, adenocarcinoma(p=.024) and first 10 experience cases(p=0.048) remained significant for recurrence. Conclusions: Early stage CC treated with RRH has a unique pattern of recurrence with carcinomatosis that results in shortened DFS. Recurrences were associated with adenocarcinoma and first 10 cases of surgeon experience.